Conservation overstretch and long‐term decline of wildlife and tourism in the Central African savannas. Issue 2 (28th December 2021) - Scholte, Paul; Pays, Olivier; Adam, Saleh; Chardonnet, Bertrand; Fritz, Hervé; Mamang, Jean‐Baptiste; Prins, Herbert H. T.; Renaud, Pierre‐Cyril; Tadjo, Patrick; Moritz, Mark
Abstract: When in 2010 the world's governments pledged to increase protected area coverage to 17% of the world's land surface, several Central African countries had already set aside 25% of their northern savannas for conservation. To evaluate the effectiveness of this commitment, we analyzed the results of 68 multispecies surveys conducted in the seven main savanna national parks in Central Africa (1960–2017). We also assembled information on potential drivers of large herbivore population trends (rainfall and number of rangers) and on tourist numbers and revenues. In six out of the seven parks, wild large herbivore populations declined dramatically over time, livestock numbers increased severalfold, and tourism, the pillar under a once thriving local wildlife industry, collapsed. Zakouma National Park (Chad) stood out because its large herbivore populations increased, an increase that was positively correlated with rainfall and number of rangers (a proxy for management inputs). With increasing insecurity and declining revenues, governments find themselves confronted with too few resources to protect vast areas. To deal with this conversation overstretch, we propose to extend the repeatedly promoted solutions––scaled up funding, enhanced management––with a strategic retreat, focusing scarce resources on smaller areas to save wildlife in the Central African savannas. Abstract : Article Impact Statement : Conservation overstretch––too few resources to protect vast areas––results in wildlife declines in Central Africa. Abstract : Sobredimensionamiento de la Conservación y la Declinación a Largo Plazo de la Fauna y el Turismo en las Sabanas de África Central Resumen: Cuando los gobiernos del mundo se comprometieron en 2010 a incrementar la cobertura de áreas protegidas al 17% de la superficie terrestre del planeta, varios países del centro de África ya habían dispuesto el 25% de sus sabanas ubicadas al norte de la región para la conservación. Para evaluar la efectividad de este compromiso, analizamos los resultados de 68 censos multiespecies realizados en los siete parques nacionales principales de la sabana en África Central (1960‐2017). También ensamblamos información sobre los causantes principales de las tendencias poblacionales de los grandes herbívoros (lluvias, número de guardaparques) y sobre las cifras e ingresos del turismo. En seis de los siete parques, las poblaciones de los grandes herbívoros silvestres declinaron dramáticamente con el tiempo, el número de cabezas de ganado incrementó varias veces y el turismo, el pilar de una industria faunística próspera en su momento, colapsó. El Parque Nacional Zakouma en Chad resaltó debido a que las poblaciones de herbívoros grandes incrementaron en esta localidad, un incremento que estuvo relacionado positivamente con las lluvias y el número de guardabosques (un sustituto para las aportaciones de manejo). Con el incremento en la inseguridad y la declinación de los ingresos, los gobiernos se encuentran de frente con muy pocos recursos para proteger áreas extensas. Para afrontar este sobredimensionamiento de la conservación, proponemos ampliar las soluciones que se promueven repetidamente – incrementos al financiamiento, manejo mejorado – con un repliegue estratégico, el cual enfoque los recursos escasos en las áreas más pequeñas para rescatar a la fauna de las sabanas del centro de África.